Vigilante Islamists: religious parties and anti-state violence in Pakistan - White, Joshua T. (Oxford University Press, 2025)
"This book investigates the role that Pakistan's Islamist political parties have played since the 1990s as both collaborators and competitors with violent anti-state movements. Drawing on dozens of interviews with party insiders, Urdu-language publications, and internal documents, the book explains the ways in which these small but influential parties have navigated between their interests in championing an ever-more expansive vision of Islamic law, and continuing their legitimate participation in democratic politics. It argues that the decisions of Islamist parties about whether to embrace violent anti-state movements or countenance vigilantism within their own ranks are shaped in part by their religious and ideological traditions, but more so by their own vulnerabilities-both to radical fringe groups, and to Pakistan's own powerful security services. The book's five case studies, spanning three decades, map these vulnerabilities and motivations within the country's leading Islamist parties. This analysis provides insights into the inner workings of prominent Islamist organizations, and the strategies that they select to endorse, or quietly undermine, anti-state militants. More broadly, this volume sheds light on how and when Islamist parties in South Asia, Southeast Asia, and the Middle East might decide to collaborate with radical movements that violently challenge the existing political order"-- Provided by publisher